Desain Pengembangan Kurikulum Pendidikan Agama Islam - Mahrus Mahrus (Jurnal Pendidikan Islam, 2021)
Design can be formulated as a deliberate process of thinking, planning and selecting the parts, techniques, and procedures that set a goal. Challenges to Islamic religious education include a moral crisis and a personality crisis. Therefore, Islamic religious education is required to be able to equip students with the moral, personality, quality and maturity of life to live a multi-cultural nation life, which is currently hit by an economic crisis in order to livepeacefully in the world community.In an effort to develop an Islamic education curriculum to overcome various challenges and problems, it is necessary to pay attention to several aspects including strategies, methods, materials, Islamic religious teacher resources, facilities, teaching media and supporting instruments.Taking into account the demands of the globalization era of Islamic religious education in madrasas and public schools, it is necessary to implement several strategies, including: First, perfecting the religious education curriculum so that the subject matter reaches a proportional and functional composition but does not burden students. Second, combining religious material with character education materials such as PPKn or other related subjects can also erode thedichotomy of knowledge. Third, creating a religious condition in the school environment